The Effect of Management Order on Work Systems and Efficiency of the Firms in Small and Medium Sized Projects - Khalil, Mohamed Alhadi (Journal of Islamic World and Politics, 2018)
This paper focuses on the role of SMEs in shaping the economy of developing and developed countries, contributing to the elimination of unemployment rates in many countries and achieving a certain level of income, in addition to their social role such as achieving social solidarity and social advancement. In the administrative system of such projects caused their failure and failure to cope with progress and achievement of goals. The paper reached some conclusions, the most important of which are: 1-The weakness of the efficiency of the administrative system in the institutions of the subject matter and the study, and this through the availability of the necessary number of workers, due to the failure to plan ahead of work and develop appropriate measures. 2-Low follow-up of working individuals from the discrimination of the owners of skills and experience, through the work of appropriate training and rehabilitation programs that contribute to the success of the institution or project. 3-Lack of motivation and lack of opportunities for entrepreneurs and entrepreneurs, especially leaders, to express their inventions, which contribute to the success of those projects and developed.